Unilateral Subconjunctival and Retrobulbar Hemorrhage Secondary to Brodifacoum Toxicity in a Dog - Sonia E. Kuhn; Diane V. H. Hendrix (Case Reports in Veterinary Medicine)
An 8-year-old spayed female mixed-breed dog was presented for an acute onset of bleeding around the left eye. Mild exophthalmos and massive subconjunctival hemorrhage on the globe and nictitating membrane were present in the left eye. Retrobulbar hemorrhage was suspected, and pain was implied on opening of the mouth because the patient resisted and vocalized. No other abnormalities were found on ophthalmic or physical examination. Further questioning of the owner confirmed potential brodifacoum ingestion, and prothrombin time and partial thromboplastin time were both markedly elevated. Treatment with oral vitamin K1 was implemented, and the subconjunctival hemorrhage was significantly improved within a few days of instituting treatment. All clinical signs of coagulopathy were completely resolved within 4 weeks of presentation. Coagulopathy secondary to brodifacoum ingestion can manifest as severe unilateral bulbar and nictitating membrane subconjunctival hemorrhage and exophthalmos due to retrobulbar hemorrhage without other clinical signs.